2008
DOI: 10.1002/pros.20768
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lymphatic invasion by peritumoral lymphatic vessel density in prostate biopsy cores

Abstract: PTLD in prostate biopsy specimens assessed by immunohistochemistry using D2-40 antibody could be a useful parameter for predicting lymphatic spread of clinically localized prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…We confirmed in a previous study that lymphatic parameters such as the average or maximal PTLD determined using the D2-40 antibody, which is specific for lymphatic but not vascular vessels, in positive biopsy cores were significant and independent predictors of lymphatic invasion in surgical specimens [8] , and recon- firmed in the present study the impact of the PTLD values on lymphatic invasion in surgical specimens ( table 2 ). This means that prediction of BCR on the basis of the lymphatic parameters used for biopsy tissue samples might be possible.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…We confirmed in a previous study that lymphatic parameters such as the average or maximal PTLD determined using the D2-40 antibody, which is specific for lymphatic but not vascular vessels, in positive biopsy cores were significant and independent predictors of lymphatic invasion in surgical specimens [8] , and recon- firmed in the present study the impact of the PTLD values on lymphatic invasion in surgical specimens ( table 2 ). This means that prediction of BCR on the basis of the lymphatic parameters used for biopsy tissue samples might be possible.…”
Section: Discussionsupporting
confidence: 78%
“…Because this antibody does not react with the endothelium of blood vessels, lymphatic vessels can be differentiated from blood vessels [9] . PTLD assessed by using the D2-40 antibody for immunostaining has been suggested to correlate with the lymphatic invasion in radical prostatectomy specimens and lymph node metastasis [11,12] , and we found that the PTLD values in biopsy cores were independent predictors of the lymphatic invasion in prostatectomy specimens [8] .…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…1,2 Many studies have shown that there is a relationship between malignant tumor metastases and increased density of intratumoral lymphatic vessels. [3][4][5][6] Most of these results come from the immunohistochemical staining of intratumoral lymphatic vessels in sections of tumor specimens, and the specific biomarkers used for lymphatic vessels are several proteins, which are expressed in lymphatic endothelial cells (LECs), such as the mucin-type transmembrane protein Podoplanin, 7 lymphatic vessel endothelial hyaluronan receptor-1 (LYVE-1), 8 homeobox transcription factor Prox-1, 9 and vascular endothelial growth factor receptor-3 (VEGFR-3). [10][11][12] Although the in vitro method is the current gold standard for the study of intratumoral lymphatic vessels, the occurrence and development of lymphatic vessels cannot be dynamically observed.…”
Section: Introductionmentioning
confidence: 99%